THE ROLE AND SIGNIFICANCE OF PEDAGOGICAL RESEARCH IN THE MODERN EDUCATION SYSTEM (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis highlights the theoretical and practical significance of pedagogical research in the development of the modern education system. It analyzes the essence of pedagogical research, its methodological foundations, and its close relationship with educational qualityand innovative processes. In addition, based on scientific sources, the paper substantiates the role of pedagogical research in updating educational content, improving teaching methods, and developing the professional competencies of pedagogical personnel under contemporary educational conditions.
Keywords: pedagogical research, methodology, quality of education, scientific inquiry, innovative education, competency-based approach.